The Influence of Financial Performance, Corporate Governance, and Trading Volume on Islamic Stock Prices (Case Study on ISSI BUMN Sector in 2011-2023): - Wulandari, Amelia; Riyan Andni (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: The rapid growth of the sharia capital market in Indonesia reflects increasing public interest in sharia-compliant investments, driven by stable economic growth, political stability, and supportive government policies. By examining these variables, this research aims to provide a comprehensive understanding of the factors shaping sharia stock prices in a dynamic economic environment, offering valuable insights for investors, policymakers, and stakeholders to enhance the development of the sharia capital market. Methods: This study uses a quantitative approach to analyze the effects of financial performance, corporate governance, and trading volume on sharia stock prices in the ISSI-listed BUMN sector during 2011-2023. The analysis employs multiple linear regression on panel data, supported by validity tests and model selection techniques, to ensure robust and reliable results. Results: Financial performance measured by Return on Assets (ROA) has a significant positive impact on sharia stock prices in the ISSI-listed BUMN sector, aligning with signaling theory, which highlights good performance as a positive signal for investors. Similarly, good corporate governance (GCG), reflected in a high Corporate Governance Perception Index (CGPI), significantly boosts sharia stock prices, while increased trading volume shows a negative effect, possibly due to selling pressure, emphasizing the need for careful interpretation of market signals. Conclusion and suggestion: Financial performance and corporate governance positively influence sharia stock prices, while trading volume negatively impacts them due to market pressure or speculation. Companies should enhance governance and profitability, while regulators strengthen trading oversight to ensure market stability.